(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article discusses the etymology and definitions of the concepts "tautology" and "pleonasm", widely used in linguistics and rhetoric. The historical roots of the terms, their development in the context of philological thought, as well as differences and similarities in modern linguistic usage are analyzed. Special attention is paid to the relationship between these concepts, their functional load and their role in the structure of the utterance. The purpose of the study is to deepen the understanding of the terms, which will allow for a more accurate interpretation of speech phenomena and avoid their stylistic errors.